(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Among gram-negative microorganisms Pseudomonas aeruginosa is the most common bacteria identified in different clinical specimens of hospitalized patients. A few studies have been conducted in Saudi Arabia regarding antibiotic susceptibility pattern. The purpose of this study was to evaluate the current levels of antibiotic susceptibility and to assess the resistance pattern of antibiotics among the clinical isolates of P. aeruginosa in the King Khalid Hospital, Alkharj, Kingdom of Saudi Arabia. This study was carried out during January, 2015 to May, 2015. A total of 180 different specimens such as sputum, urine, pus swabs, wound swabs etc. were collected from different patients admitted to the hospital. Thirty (30) clinical isolates of P. aeruginosa were isolated from different specimens of the patients suspected of having respiratory tract infection, urinary tract infection, wound infections, etc. The antibiotic susceptibility profiles of all the isolates were determined using Kirby-Bauer disk diffusion method. Piperacillin-tazobactam was found to be the most active antimicrobial agent with 96.7% susceptibility followed by cefepime (83.3%), ceftazidime (83.3%), and ciprofloxacin (76.7%). All isolates were resistant to ertapenem, cefuroxime, cefoxitin and nitrofurantoin. Anti-bacterial treatment strategies should focus on P. aeruginosa, for which the prevalence rates are increasing every year. The usage of piperacillin-tazobactam, cefepime, ceftazidime and ciprofloxacin must be reserved and only be given to the patients after susceptibility test to reduce the resistance of P. aeruginosa against these agents. Dhaka Univ. J. Pharm. Sci. 19(1): 77-82, 2020 (June